Physical Activity Behavior During and After COVID-19 Stay-at-Home Orders-A Longitudinal Study in the Austrian, German, and Italian Alps - Stefanie E. Schöttl; Martin Schnitzer; Laura Savoia; Martin Kopp (Frontiers Media S.A., 2022)
BackgroundIn Alpine regions, which are very similar due to their topographical location and their wide-ranging sports offerings, the restrictions on sports activities during the COVID-19 pandemic differed in type and level: while in some regions (Tyrol, South Tyrol, Trentino), all sports activities were forbidden except for walking near the home, in other regions (Upper Bavaria, Vorarlberg), people were allowed to go hiking and running during the first lockdown.ObjectiveThe aim of this study was to investigate the change in physical activity (PA) behavior in different Alpine regions (Upper Bavaria, Vorarlberg, Tyrol, South Tyrol, Trentino) over four periods in 2020, to examine the effects of COVID-19 measures of varying severity on PA behavior and to identify factors associated with a change in PA over time.MethodsA retrospective online survey was conducted (N = 2975) from December 2020, to January 2021. Using the questionnaire of the Eurobarometer 472 study, PA behavior was measured over four periods: before COVID-19 (March), during the first lockdown (March and April), during the relaxed period (May-October) and during the second lockdown (November and December) in 2020.ResultsDuring the first (M = 5.0h, SD = 4.5) and the second lockdowns (M = 4.9h, SD = 4.3), the participants (age: 42 years, overly active in sports) engaged less in sports than before (M = 5.9h, SD = 4.8) and during the relaxed period in summer (M = 6.4h, SD = 5.0) (average number of hours per week being physically active). A larger percentage of participants from Alpine regions with severe restrictions (Tyrol, South Tyrol, Trentino) decreased their PA during the first lockdown as compared to participants from Upper Bavaria and Vorarlberg with a less strict first lockdown. Those with psychological distress, male participants, and individuals with decreased physical health and less free time during COVID-19 were more likely to reduce their PA.ConclusionsDespite a short-term negative effect of COVID-19 restrictions on exercise participation during lockdowns, the majority of respondents returned to their original levels of PA during the relaxed COVID-19 phases. As a comparison of Alpine regions shows, particularly severe COVID-19 measures seem to have reduced PA with potential negative health effects. For the future, policy makers and sports organizations should collaborate to support the population in their PA behavior during pandemics to outweigh restrictions.